The Influence of Learning Media on Learning Motivation in Class IV Students at Siburbur Elementary School, Halongonan District, South Tapanuli Regency with Indonesian Language Subjects - Panggabean, Dewi Sartika; Shaleha, Kharida (Cattleya Darmaya Fortuna, 2022)
The results of the study indicate that the level of use of learning media belongs to the good category in terms of indicators of visual media, audio media and audio visual media. The level of student learning motivation is classified as very high in terms of indicators that excite students, provide realistic expectations, provide incentives, and direct student behavior. The results of the analysis and hypothesis testing indicate that there is a significant influence of learning media on the learning motivation of fourth grade elementary school students with Indonesian language subjects.